Molecular structure of 8-hydroxy-1-methylquinolinium iodide hydrate in crystal and solution - Barczyński, Piotr; Komasa, Anna; Ratajczak-Sitarz, Małgorzata; Katrusiak, Andrzej; Brzezinski, Bogumil (My University, 2006)
8-Hydroxy-1-methylquinolinium iodide monohydrate [(C10H10NO)I-+(-) H2O] has been studied by X-ray diffraction, FF-IR, H-1 and C-13 NMR spectroscopy. In the crystalline state, the iodide anion is hydrogen-bonded to the water molecule, which in turn is hydrogen bonded to the 8-OH group of the 8-hydroxyquinolinium ring, forming of a symmetric dimer. In acetonitrile and DMSO-d(6) the hydrate assumes a new structure due to almost complete dissociation of the water molecule from the complex structure. In acetonitrile the 8-OH group is hydrogen-bonded to the iodide anion, whereas in DMSO-d(6) it forms the hydrogen bond with the solvent molecules. This 8-OH... O(DMSO-d(6)) hydrogen bond is the strongest within the structure of the hydrate.
Keywords: 8-hydroxy-1-methylquinolinium cation; intermolecular hydrogen bonds; halides; X-ray structure; hydrates; FT-IR, H-1 NMR, C-13 NMR